Development of Cellular Cast Structures for Improving Heat Transfer in Thermal Energy Storage Systems - K. Naplocha; J. Grzęda; O. Trzaska; N. M. Raźny; A. Dmitruk (Archives of Metallurgy and Materials)
For improving heat transfer in the thermal energy storage system (TES), cast aluminum cellular structures were designed, optimized, and produced by investment casting. The pattern was 3D printed from polylactide (PLA) polymer and then subjected to molding and heat treatment. Selected casting parameters, i.e. temperature of the mold and poured metal, as well as low pressure (vacuum), allowed to production of a complex, thin-walled casting. To evaluate the effectiveness of the structures (enhancers), a lab-scale heat accumulator was constructed and filled with phase change material (PCM) composed of KNO3 and NaNO3 salts. Thermal cycling, including charging and discharging of the accumulator, was analyzed and compared between systems with pure PCM bed and the one equipped with the produced enhancer. To protect aluminum casting against corrosion with molten salts, nickel plating was applied. Process parameters, such as plating process time and nickel subcoating application time, were determined. Microscopic observations confirmed high-quality, continuous coating on aluminum casting surfaces with characteristic microgrooves remaining after the printed pattern.